Infection post debridement before and after golden period of open fracture of the lower leg grade Ill A and Ill B. - Armis, Armis (Universitas Gadjah Mada, 1995)
All open fractures especially open fracture of the lower leg grade III A and III B, should be assumed to be contaminated, therefore they tend to be infected. The time of intervention is one of the risk factors of infection complication.A descriptive analysis has been conducted aiming at evaluate the occurrence of infection and the time of treatment on patients with open fracture of the lower leg grade III A and III B. In this study 102 cases (80 males and 22 females) who had open fracture of the lower leg grade III A and III B were admitted to Dr. Sardjito General hospital, Yogyakarta. Patients were evaluated according to the inclusion and exclusion criteria. Out of fifty-four cases underwent intervention before 8 hours after injury (within golden period) 25 cases (46,29%) had been infected. The rest (48 cases) who had treatment after 8 hours since trauma, 83,33% (40 cases) were infected.A statistical analysis (X2 = 13,520, df=1 and p < 0,001) showed that there was significant difference of infection complication of open fracture of the lower leg grade III A and III B and the intervention between within and beyond golden period.Key words: open fracture - tibia fracture - infection - golden period - debridement